Interview with Richard W. Scott: «You Need to Think Hard about the Difference between Approaching a Question as an Economic Sociologist Versus an Organization Sociologist» (translated by Dana Assalauova) - William Richard Scott (Journal of Economic Sociology, 2012)
Detailed description in the text